2019
DOI: 10.1200/jco.2019.37.15_suppl.e14670
|View full text |Cite
|
Sign up to set email alerts
|

Implication of DYRK1B kinase in dormant glioblastoma cancers and utilization of DYRK1B inhibitors as a novel therapeutic strategy for glioblastoma.

Abstract: e14670 Background: A major determinant of cancer resistance and recurrence is the presence of quiescent cancer cells. It has long been known that quiescent cancers are resistant to a wide variety of anti-cancer therapeutics relative to actively proliferating cells. However, the presence and relative size of the quiescent compartment is not revealed by standard H&E staining and morphological tumor analysis and, therefore, the data demonstrating its importance and prevalence by tumor type are lacking. DYRK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been shown that proteins involved in main cell metabolic processes can be altered in diseases such as cancer, especially in those involved in processes that promote proliferation and survival. The presence of DYRK1B in glioblastoma, which has been characterized for this specific type of cancer (Vilenchik et al, 2019), and which has been stably found in clinical samples, control β-actina, determinado por Western blot. c-d) Porcentaje de células positivas para ALDH1A1 y DYRK1B con respecto a su patrón de expresión observado.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that proteins involved in main cell metabolic processes can be altered in diseases such as cancer, especially in those involved in processes that promote proliferation and survival. The presence of DYRK1B in glioblastoma, which has been characterized for this specific type of cancer (Vilenchik et al, 2019), and which has been stably found in clinical samples, control β-actina, determinado por Western blot. c-d) Porcentaje de células positivas para ALDH1A1 y DYRK1B con respecto a su patrón de expresión observado.…”
Section: Discussionmentioning
confidence: 99%
“…DYRK1B is overexpressed in several cancer types and maintains cellular quiescence . Moreover, DYRK1B can enhance cancer cell survival by upregulating antioxidant gene expression and reducing intracellular levels of reactive oxygen species. , It is well documented that either genetic depletion of DYRK1B or its pharmacological inhibition leads to the cell cycle re-entry and apoptosis of DYRK1B-expressing quiescent cancer cells, which brings DYRK1B inhibitors in focus of novel highly potent cancer therapies. At the same time, the inhibition of the DYRK1A kinase, which has high homology to DYRK1B in its active site yet different functions and tissue distribution, bears risks of adverse drug reactions because DYRK1A is expressed in multiple tissues and is involved in a plethora of housekeeping cellular processes .…”
Section: Introductionmentioning
confidence: 99%